Sacre bleu [compact disc, unabridged] : a comedy d'art - Moore, Christopher, 1957- (HarperAudio, 2012)
From repeat New York Times bestselling author Christopher Moore comes a love story, the portrait of a young artist, the portrait of the young artist's girlfriend, a mystery, a thriller, and a comedy-all about the color blue.